Analysis of the GH content within archived dried blood spots of newborn screening cards from children diagnosed with growth hormone deficiency after the neonatal period - Binder, Gerhard; Hettmann, S.; Weber, K.; Kohlmüller, Dirk; Schweizer, R. (Growth hormone & IGF research, 2011)
Objective - It is unknown whether GH secretion of children with growth hormone deficiency (GHD) is already diminished at birth. We aimed to determine the GH content within archived dried blood spots of newborn screening cards from children diagnosed with GHD at childhood. - Design - At our hospital, all children with the diagnosis of GHD and an actual age <10years were identified. For 16 patients (mean age, 7.4years; range, 1.0-9.7), screening cards were available. The archived dried blood from the first 48 to 96h of life was eluated in buffer of a highly sensitive hGH-ELISA to measure the GH content. Reference values were calculated based on 600 anonymous newborn screening cards of different ages. - Results - Median GH content within the archived dried blood spots of the reference had declined by 30% during the first year and by further 35% during the next 8.5years of storage. After correction for time of storage, four out of the 16 archived dried blood spots of the GHD children contained low amounts of GH (≤5th percentile). Diminished GH secretion at birth was absent in isolated GHD, but associated with multiple pituitary hormone deficiency (MPHD) (P=0.0013), ectopic neurohypophysis (P=0.0013), lower GH test peak values (P=0.02) and higher weight at diagnosis (P=0.015). - Conclusions - Children with isolated GHD have normal GH secretory capacity during the first week of life while the majority of children with MPHD and pituitary malformation were GH deficient immediately after birth.